Breathing Hearts : Sufism, Healing, and Anti-Muslim Racism in Germany. - Selim, Nasima (New York, NY : Berghahn Books, Incorporated, 2024)
No detailed description available for "Breathing Hearts".
Intro -- Contents -- Illustrations -- Preface - The Ethnographer Breathes -- Acknowledgments -- Note on Transliteration and Translation -- Abbreviations -- Introduction - "A Sufi Is Someone Who Breathes Well": The Ways of Breathing Hearts -- Chapter 1 - The Unseen Neighbors and a Dual Apprentice: Silsila, or Drawing the Lines of Transmitting Breath -- Chapter 2 - "Why Do I Suffer and What Should I Do?": The Desire Lines of Sufi Breathing-Becoming -- Chapter 3 - Techniques of Transformation: Subtle-Material Bodies in Dhikr and Other (Breathing) Practices -- Chapter 4 - "There Must Be Something Else": The In-between World of Healing Secular and Religious Suffering -- Chapter 5 - Participation in the Real: The Healing Power of Breath, Words, and Things -- Chapter 6 - "The Right-Wing Attacks Our Mosques and Our Muslim Brothers Do Not Consider Us to Be Real Muslims!": The (Anti-)Politics of Breathing Hearts -- Conclusion - Lessons from the Breathing, Wayfaring Hearts -- Epilogue - Sufi Breathing In the Pandemic Ruins of (Anti-Muslim) Racism -- Glossary -- References -- Index -- Blank Page.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books